Advanced Polycrystalline γ′-Strengthened CoNiCr-Based Superalloys - Neumeier, Steffen; Freund, Lisa; Bezold, Andreas; Köbrich, Manuel; Vollhüter, Jan; Hausmann, D.; Solis, C.; Stark, A.; Schell, N.; Pyczak, F.; Felfer, Peter; Gilles, R.; et al. (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2024)
Novel compositionally complex CoNiCr-based superalloys with excellent mechanical properties have been developed, which combine the multiprincipal element nature of high-entropy alloys with the precipitation strengthening in superalloys. A series of advanced polycrystalline γ′-strengthened CoNiCr-based superalloys, called CoWAlloys, with varying contents of Al, W, Ti, Ta, Mo, and Nb are investigated in terms of microstructure, thermophysical properties, yield, and creep strength. The microstructure of all CoWAlloys consists of an fcc solid solution matrix phase (approximate γ composition in at. pct: 50Co–20Ni–20Cr–10X (X = other alloying elements)), which is strengthened by a multicomponent γ′ (Ni,Co)3(Al,Ti,Ta,W,Nb)-based precipitate phase with a very high-volume fraction of around 60 vol pct (approximate γ′ composition in at. pct: 45Ni–30Co–25X). These alloys have high solidus temperatures above 1300 °C and moderate γ′ solvus temperature between 985 °C and 1080 °C leading to a large processing window. The increasing content of γ′-forming elements Ti, Ta, W, and Nb decreases this window, but increases the γ/γ′ lattice misfit and the anti-phase boundary energy, which contribute to a significantly higher yield and creep strength. Their properties are discussed in comparison with conventional polycrystalline Ni-base superalloys and so-called L12-strengthened high-entropy alloys, revealing that the creep strengths of the CoWAlloys are significantly higher. This is due to the reduced strain rate sensitivity of the CoWAlloys due to different underlying deformation mechanisms: By increasing the anti-phase boundary energy, a transition to stacking fault shearing and microtwinning occurs, which leads to the enhanced creep strength. Based on these results, guidelines and strategies for the design of next-generation advanced high-temperature polycrystalline superalloys are proposed. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-03-15

Anomalous Work Hardening Behavior of a Single Crystalline Co-Base Superalloy - Bezold, Andreas; Volz, Nicklas; Xue, Fei; Neumeier, Steffen; Göken, Mathias (Alloys, 2022)
The defect evolution associated with an anomalous work hardening behavior of a single crystalline quaternary Co-Al-W-Ta superalloy at 950 °C was investigated by transmission electron microscopy. As plastic deformation is initially confined to the γ matrix channels, a plateau arises in the stress-strain curve after yielding. At about 1% plastic strain, extensive shearing of the γ′ precipitates under superlattice stacking fault formation occurs leading to extreme work hardening rates up to 12 GPa and a total increase in stress of about 200 MPa. Additional investigations on the temperature and strain-rate dependence of the anomalous work hardening behavior reveal the significance of diffusion and segregation processes on the stress-strain curve and the work hardening behavior.
Keywords: superalloy; yielding behavior; work hardening; transmission electron microscopy (TEM); high-temperature deformation

Design of a Co–Al–W–Ta Alloy Series with Varying γ′ Volume Fraction and Their Thermophysical Properties - Volz, Nicklas; Xue, Fei; Bezold, Andreas; Zenk, Carolin; Fries, Suzana G.; Schreuer, Juergen; Neumeier, Steffen; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2021)
The γ′ volume fraction is a key parameter in precipitation-strengthened Co- and Ni-base superalloys and mainly determines the alloys’ properties. However, systematic studies with varying γ′ volume fractions are rare and the influence on thermal expansion has not been studied in detail. Therefore, a series of six Ta-containing Co-based alloys was designed with compositions on a γ–γ′ tie-line, where the γ′ volume fraction changes systematically. During solidification, Laves (C14-type) and µ (D85-type) phases formed in alloys with high levels of W and Ta. Single-phase γ or two-phase γ/γ′ microstructures were obtained in four experimental alloys after heat treatment as designed, whereas secondary precipitates, such as χ (D019-type), Laves, and μ, existed in alloys containing high levels of γ′-forming elements. However, long-term heat treatments for 1000 hours revealed the formation of the χ phase also in the former χ-free alloys. The investigation of the thermal expansion behavior revealed a significant anomaly related to the dissolution of γ′, which can be used to determine the γ′ solvus temperature with high accuracy. Compared to thermodynamic calculations, differential scanning calorimetry (DSC) and thermal expansion analysis revealed a larger increase of the γ′ solvus temperatures and a lesser decline of the solidus temperatures when the alloy composition approached the composition of the pure γ′ phase.

High-Temperature CoNi-Based Superalloys Strengthened by γ′-(Ni,Co)3(Cr,Al,Ti,X): The Effect of Refractory Elements - Liang, Zhida; Paul, Jonathan D. H.; Stark, Andreas; Bezold, Andreas; Neumeier, Steffen; Göken, Mathias; Pyczak, Florian (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2022)
Recent research on Co-based and CoNi-based alloys revealed that the Co–Al–W-system provides interesting properties, however, the high content of W addition triggers high mass density of alloys which limits its industrial application. Therefore, new high temperature superalloys based on the Co–Ni–Al–Ti-system with high content Cr and strengthened by γ′-(Ni,Co)3(Cr,Al,Ti) precipitates, have been developed, and the effect of different refractory element additions was investigated. STEM-EDS and HEXRD were employed to determine the elemental partitioning behavior and the lattice misfit between the γ and γ′ phases. Ta and Nb strongly concentrate within the γ′ phase, whereas Mo weakly partitions to the γ phase. W distributes equally between the γ and γ′ phases. These new superalloys have an unexpectedly high positive misfit compared with some conventional Ni-based superalloys and Co-based superalloys. Nb and Ta additions increase the lattice misfit further, while Mo and W decrease the lattice misfit. The effect of refractory elements alloying on the yield stress at room temperature was evaluated by analyzing the contributions of different strengthening mechanisms. Alloying with Nb or Ta significantly improves precipitation strengthening by increasing the antiphase boundary energy. Mo has the highest solid solution strengthening effect in the γ phase, followed by W. Compared with some conventional Ni-based superalloys, the investigated new CoNi-based superalloys exhibited better mechanical properties at high temperature, which indicates that these compositionally complex alloys are possible candidates for high temperature applications. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-09-30

Influence of Cu Addition and Microstructural Configuration on the Creep Resistance and Mechanical Properties of an Fe-Based alpha/alpha '/alpha '' Superalloy - Morales, Luis Angel; Bezold, Andreas; Förner, Andreas; Holz, Hendrik; Merle, Benoit; Neumeier, Steffen; Körner, Carolin; Zenk, Christopher (Advanced Engineering Materials, 2023)
Introducing Cu nanoparticles is an effective mechanism for strengthening and toughening Fe-based materials such as ultra-high-strength steels. Herein, the effect of Cu on the mechanical properties of a novel Fe-based alpha/alpha '/alpha '' superalloy is studied. Compared to a Cu-free reference alloy, nanoindentation reveals an increase in hardness, which was associated with the formation of Cu nanoparticles. Both alloys show room temperature (RT) compressive plastic strain at maximum stress greater than 8%, irrespective of the heat-treatment. At RT and at 750 degrees C, the Cu-containing alloy exhibits a slightly higher strength, but the heat treatment has a more significant impact: A configuration of alpha-matrix and intermetallic alpha '/alpha ''-phases forming an interpenetrating network is superior to a state with isolated precipitates. This difference vanishes in monotonic creep experiments, and under the same conditions, the Cu-containing alloy exhibits a twice as high creep rate despite a slightly higher precipitate fraction. This is linked to a higher lattice misfit and faster-coarsening kinetics. Post-mortem transmission electron microscopy analysis of the creep-deformed specimens identifies dislocation bypass as the dominant deformation mechanism. However, the presence of 110 dislocations in the interfacial networks and evidence of dislocation activity within alpha '/alpha '' precipitates suggest the occurrence of shearing events.
CRIS-Team WoS Importer:2023-03-03

Influence of the γ′ Volume Fraction on the High-Temperature Strength of Single Crystalline Co–Al–W–Ta Superalloys - Xue, Fei; Bezold, Andreas; Volz, Nicklas; Kirchmayer, Andreas; Zenk, Christopher; Neumeier, Steffen; Göken, Mathias (Crystals, 2023)
Understanding the influence of γ′ and secondary-phase fractions on the mechanical properties of superalloys is very important to optimize these high-strength materials. So far, this has not been systematically investigated for the novel class of Co-based superalloys. In this study, a Co–Al–W–Ta model alloy series was designed with compositions of γ/γ′ on the tie-line and an increasing γ′ volume fraction of up to 70% after heat treatment at 900 °C, while a few alloys are unexpectedly out of γ/γ′ two-phase region with an additional secondary phase fraction of up to 15%. The high-temperature strength and creep properties were evaluated by compression tests up to 1050 °C and compressive creep experiments at 950 °C, respectively. At temperatures of up to 1050 °C, an increasing γ′ volume fraction consistently increased the yield strength, which was not dramatically changed by the presence of secondary phases. Significant work hardening was found in alloys with γ′ volume fractions of 65–70% during compression testing, but not in alloys with either a lower γ′ volume fraction (<50%) or a high fraction of secondary phases ( 15%). Similar to the yield strength, the creep strength also increased continuously with the γ′ volume fraction, but was greatly reduced with an increasing fraction of secondary phases. The best creep performance at 950 °C and 200 MPa was found in the alloy with the highest γ′ volume fraction and no secondary phases. At higher creep stresses, rafting contributed significantly to the hardening and, again, the alloy with a high γ′ volume fraction and a small amount of secondary phases exhibited the highest strength.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Co-based superalloys; compression test; creep; rafting; stacking faults; transmission electron microscopy

In Situ Investigation of TCP Phase Formation, Stress Relaxation and gamma/gamma ' Lattice Misfit Evolution in Fourth Generation Single Crystal Ni-Base Superalloys by X-Ray High Temperature Diffraction - Bezold, Andreas; Stone, H. J.; Rae, C. M. F.; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2022)
In nickel-based superalloys, the lattice misfit between the gamma and gamma' phases and the propensity to TCP phase formation at service temperatures critically influence the microstructural evolution that takes place and hence the resultant mechanical properties. In this work, the lattice misfits of a series of highly alloyed Ru-containing 4th generation Ni-base superalloys are investigated by in situ X-ray diffraction (XRD) at high temperature. While the lattice misfit values of all alloys range between - 0.3 and - 1.3 pct at room temperature, they show an atypical temperature dependence, becoming less negative above 900 degrees C. In situ XRD measurements at 1100 degrees C reveal that the majority of the internal coherency stresses are already relieved after two hours. This is particularly pronounced for the alloys that have both a lattice misfit larger than vertical bar 0.6 vertical bar pct at 1100 degrees C and are prone to TCP phase formation. However, throughout the relaxation of the internal coherency stresses the lattice misfit remains fairly constant. Due to the similar chemical compositions of the alloys studied, qualitative guidelines for an optimum lattice misfit magnitude are developed by comparing the lattice misfit values with previous creep experiments. Our results indicate that no universal optimal lattice misfit value exists for these alloys and the value strongly depends on the applied creep conditions.
CRIS-Team WoS Importer:2022-05-27

Laser powder bed fusion of FeCoBSiNb-Cu bulk metallic glass composites: Processing, microstructure and mechanical properties - Luo, Ning; Huber, Florian; Ciftci, Nevaf; Wahl, Larissa; Bezold, Andreas; Neumeier, Steffen; Uhlenwinkel, Volker; Travitzky, Nahum; Schmidt, Michael; Zenk, Christopher; Körner, Carolin (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2022)
Fe–Co–B–Si–Nb bulk metallic glasses are prone to the formation of micro-cracks during laser powder bed fusion (LPBF) additive manufacturing. Introducing ductile Cu into Fe–Co–B–Si–Nb bulk metallic glass alloy system rich with Fe and Co could be a promising solution to reduce or even eliminate micro-cracks since there is almost no miscibility of Cu in Fe and Co. In this work, processing, microstructure and mechanical properties of Cu-containing (Fe0.6Co0.4)0.75B0.2Si0.0596Nb4 (at.%) bulk metallic glass composites (BMGCs) under different laser power and scanning speed by LPBF are investigated in detail. A moderate area energy density facilitates the fabrication of highly dense (relative density: up to ∼99.5%) and almost crack-free (crack density: ∼0.1 mm−1) FeCoBSiNb–Cu bulk samples. These bulk samples possess an interpenetrating composite microstructure mainly composed of an amorphous Fe(Co)-rich phase and a crystalline Cu-rich phase. A crystalline Cu-rich phase is distributed relatively homogeneously in an amorphous phase and helps to reduce and even eliminate micro-crack formation during LPBF processing. Also, the Cu-rich phase has the effect of a heat sink and thus speeds up heat dissipation, facilitating the formation of an amorphous phase. The microhardness of the ductile Cu-rich phase and the hard amorphous Fe(Co)-rich phase in the interpenetrating composite microstructure was evaluated. Compressive tests at room temperature indicate that the dense bulk samples exhibit a relatively high fracture strength and a large fracture strain. Additionally, bulk samples with lack-of-fusion pores show a larger fracture strain although their fracture strength is lower than that of dense bulk samples. It is concluded that the LPBF-processed FeCoBSiNb–Cu BMGCs constitute a promising wear-resistant material to be used for example as bearing materials.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Bulk metallic glass composites; Fe-based amorphous alloy; Laser powder bed fusion; Mechanical properties; Microstructure; Solidification

Localized phase transformation strengthening in CoNi-based superalloys - Bezold, Andreas; Egan, Ashton; Völkl, Julian; Karpstein, Nicolas; Gaag, Tobias; Spiecker, Erdmann; Göken, Mathias; Mills, Michael J.; Neumeier, Steffen (Scripta Materialia, 2025)
Segregation processes during high-temperature deformation can be either detrimental or beneficial in γ′-strengthened superalloys depending on which elements segregate. In intermediate CoNi-based superalloys only softening due to extensive microtwinning was observed so far. By analyzing the creep behavior of a Ta-free and a Ta-containing CoNi-based superalloy at 750 °C and 620 MPa, we show that strengthening segregation behaviors along various planar defects, including microtwinning, can be achieved in this alloy class. While both alloys deformed under planar fault formation, the Ta-containing alloy outperformed the Ta-free alloy. Atomic-scale energy dispersive spectroscopy investigations revealed strengthening effects by local phase transformations along superlattice intrinsic and extrinsic stacking faults in both alloys. However, microtwinning is enhanced in the Ta-free alloy, while it is impeded in the Ta-containing alloy. Given the faster diffusivity of Ta compared to W, kinetic effects on localized phase transformation strengthening and their subsequent influence on the creep behavior are discussed.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Creep; Segregation; Stacking fault; Superalloy; Transmission electron microscopy

Microscopic mechanism of the L12–D019 phase transformation in a Co-base single crystal superalloy - Karpstein, Nicolas; Laplanche, Guillaume; Saksena, Aparna; Zehl, Rico; Bezold, Andreas; Horst, Oliver M.; Bürger, David; Kostka, Aleksander; Zenk, Christopher; Neumeier, Steffen; Gault, Baptiste; Ludwig, Alfred; et al. (Acta Materialia, 2025)
In γ′-strengthened superalloys based on the Co-Al-W system, the stability of the γ′ phase is often limited, as it is found to transform into other phases such as B2 and D019 after long-term annealing. To explore the details behind the annealing-induced transformation from the metastable L12-γ′ phase to the thermodynamically stable D019-χ phase in the single-crystalline Co-base superalloy ERBOCo-VF60 (Co79.8Al8.9W9.0Ta2.3 in at.%), scanning transmission electron microscopy and atom probe tomography are employed. Due to the structural similarity between the L12 and D019 structures, coherent plate-shaped χ precipitates are formed in the γ/γ′ microstructure parallel to 111 planes through a shear-based transformation mechanism. While the χ phase precipitates slowly during isothermal aging, its formation can be significantly accelerated locally by coating the superalloy with a Cr-rich layer, which indirectly stabilizes the χ phase as revealed by thermodynamic calculations. This procedure allowed us to obtain an intermediate (incomplete) state of χ-phase formation in terms of both crystal structure and composition. By characterizing the partial dislocations at the tip of growing χ precipitates, the microscopic details of the shear-based cubic-to-hexagonal transformation from L12 to D019 are uncovered. The compositional aspect of the transformation involves a significant diffusion-mediated enrichment of W in the χ phase, accompanied by a simultaneous W depletion in the γ′ phase, leading to its transformation to the γ phase.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Atom probe tomography; Cobalt-base superalloys; Phase transformations; Stacking faults; Transmission electron microscopy

On the Precipitation-Strengthening Contribution of the Ta-Containing Co3(Al,W)-Phase to the Creep Properties of γ/γ′ Cobalt-Base Superalloys - Bezold, Andreas; Volz, Nicklas; Xue, Fei; Zenk, Christopher H; Neumeier, Steffen; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2020)
The creep strength of single-crystalline Co-based superalloys was found to be comparable to first-generation Ni-base superalloys. However, considerable shearing of the γ′ precipitates was observed in the early creep stages. To determine the strengthening contribution of the Ta-containing γ′-Co3(Al,W) precipitates, the creep strength of several single-crystalline Co-Al-W-Ta superalloys was determined as a function of the γ′ volume fraction at 1223 K (950 °C) and stress levels between 25 and 600 MPa. Employing a Lagneborg–Bergman–Reppich (LBR) approach, it is found that the strengthening contribution of the γ′ precipitates increases significantly with increasing γ′ volume fraction. In a Co-base superalloy that exhibits a precipitate volume fraction of about 70 pct, the γ′-strengthening contribution calculated with the LBR approach ranges between the ones observed in first-generation Ni-base superalloy CMSX-6 and second-generation Ni-base superalloy CMSX-4.
CRIS-Team Scopus Importer:2020-02-04

Quantification of the temperature-dependent evolution of defect structures in a CoNi-base superalloy - Bezold, Andreas; Volz, Nicklas; Lenz, Malte; Karpstein, Nicolas; Zenk, Christopher; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Acta Materialia, 2022)
Quantifying the individual contributions of specific deformation mechanisms to the total plastic strain is of primary importance to understand the underlying deformation behavior and assess the significance of the different mechanisms. However, this quantification is nearly impossible in Ni-base superalloys due to the inherent difficulties in determining the propagation distances of the respective shearing dislocations. In this study, the occurrence of stacking faults (SFs) at temperatures between 750 °C and 1000 °C in the single crystalline CoNi-base superalloy ERBOCo-4 provides an opportunity to systematically quantify the evolution of the defect structures as a function of temperature and strain after constant strain-rate compressive tests. The quantification approach revealed that deformation is still localized in the matrix at 750 °C. With increasing temperature, the main deformation mechanism changes to SF shearing, which contributes 74% of the total deformation during the initial yielding stage (∼ 0.3% plastic strain) at 900 °C. Deformation spreads significantly more homogeneously across the γ/γ’ microstructure with increasing plastic strain. Extremely high stacking fault densities and frequent fault interactions cause a pronounced work-hardening anomaly at 850 °C. Structural characterization on the atomic scale confirms the strengthening effect of SFs as barriers to partial dislocation propagation. A strong correlation between the possible diffusion length of segregating solutes and the operant shearing mechanisms reveals the significance of segregation on the occurring deformation mechanisms.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Co-base superalloy; Defect structures; High temperature deformation; Transmission electron microscopy; Yielding behavior

Recovery of superlattice stacking faults at high temperatures - Bezold, Andreas; Amon, L.; Karpstein, Nicolas; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Scripta Materialia, 2023)
Stacking fault shearing is commonly observed in Co-base and CoNi-base superalloys in the intermediate temperature regime between 850 °C to 1000 °C in contrast to Ni-base superalloys. In this work, we report on the significance of recovery processes after aging and creep experiments on predeformed specimens with extreme stacking fault densities. Above 950 °C, superlattice stacking faults start to recover rapidly, whereby intrinsic ones recover more quickly than extrinsic ones. Our results also reveal that the significance of stacking fault shearing in the high temperature creep regime could be higher than that indicated by traditional postmortem investigations due to recovery processes.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Co-base superalloy; Creep; Recovery; Stacking fault; Transmission electron microscopy

Segregation-induced strength anomalies in complex single-crystalline superalloys - Bezold, Andreas; Vollhüter, Jan; Karpstein, Nicolas; Lenz, Malte; Subramanyam, Aparna P.A.; Zenk, Christopher; Hammerschmidt, Thomas; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Communications Materials, 2024)
Pushing the maximum service temperature of aircraft engines and industrial gas turbines is the major pathway to improve their energy efficiency and reduce CO2 emissions. This maximum is mostly limited by the temperature capability of key-component materials, including superalloys. In this alloy class, segregation of elements facilitates plastic deformation and is generally considered to cause softening during high-temperature deformation. Here, we show that segregation-assisted processes can also lead to strengthening and induce an anomalous increase of the yield strength. Atomic-resolution transmission electron microscopy and density functional theory calculations reveal a segregation-assisted dissociation process of dislocations at precipitate-matrix interfaces in combination with atomic-scale reordering processes. These processes lead to an inhibition of athermal deformation mechanisms and a transition to stacking fault shearing, which causes the strengthening effect. Unraveling these elementary mechanisms might guide a mechanism-based alloy design of future superalloys with enhanced high-temperature capabilities.
CRIS-Team Scopus Importer:2024-02-02

Seismically induced kinking in quartz - Bestmann, Michel; Grasemann, Bernhard; Kilian, Rüdiger; Wheeler, John; Morales, Luiz F.G.; Bezold, Andreas; Pennacchioni, Giorgio (Earth and Planetary Science Letters, 2025)
Deformed quartz veins next (1–1.5 m) to an exhumed pseudotachylyte-bearing (i.e. anciently seismic) fault within the Schobergruppe (Austroalpine Crystalline Complex, Eastern Alps) contain intensely kinked quartz grains. The monoclinic symmetry of kink bands is consistent with the dextral slip sense of the fault. Cathodoluminescence images show a very high density of intragranular, sub-planar, lamellae accompanied by nanometre-scale fluid-related porosity visible in electron backscatter orientation contrast. Based on the oscillating orientation variation across subgrain boundaries (misorientation angle 1–9°) these lamellae (oriented (sub)parallel to a rhomb plane and spaced 4–10 µm apart) are identified as short-wavelength undulatory extinction microstructures (SWUE). Transmission electron microscopy reveals a high degree of recovery (low dislocation density) across the SWUE. Only grains with SWUE oriented parallel to the vein boundary are kinked. Based on detailed microstructural and crystallographic analysis, we infer the following history of kinking evolution related to the seismic cycle: (I) Deformation lamellae formed at high differential stresses preceding, or associated with, seismic rupture propagation. The initial high dislocation density within deformation lamellae provided the mechanical anisotropy in quartz required for (II) the subsequent coseismic initiation of kinking. The lamellae acted as a geometric filter that only allowed r < a> slip of dislocations parallel to the lamellae. These athermal dislocations were able to glide fast over a relatively large distance before piling up and initiating kinking during the coseismic event. Progressive build-up of dislocations resulted in deformation bands which accumulated the final misorientation angle between host domain and kink domain. (III) Residual stress during post-seismic deformation induced dynamic re-arrangement of dislocations into sub-parallel subgrain boundaries which now characterize the kink band boundary region. We suggest that kinking in quartz potentially indicates coseismic deformation and is an important mechanism for incipient strain accommodation during high strain rates.
CRIS-Team Scopus Importer:2025-09-12
Keywords: Anisotropy; Athermal dislocation; Kinking; Quartz; Seismic; Weighted burgers vector

Strain Rate-Dependent Anomalous Work Hardening of a Single-Crystalline CoNi-Base Superalloy - Vollhüter, Jan; Bezold, Andreas; Karpstein, N.; Köbrich, Manuel; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
The deformation mechanisms operating in superalloys depend on different parameters such as composition, temperature and deformation rate. So far, the transition from shearing by APB-coupled dislocations to shearing under the formation of stacking faults has been studied exclusively as a function of temperature but not as a function of the strain rate. Therefore, interrupted compression tests with strain rates between 10–3 s−1 and 10–5 s−1 were performed on the single-crystalline CoNi-base superalloy ERBOCo-4 at a temperature of 850 °C. The evolution of the defect structures has been analyzed by conventional transmission electron microscopy. A change of the deformation mechanism from APB-coupled dislocation shearing to stacking fault shearing is found to depend on the strain rate. At lower strain rates, an increased stacking fault density is associated with a higher yield strength and higher work hardening rates at the early stages of plastic deformation due to a very high stacking fault density. After approximately 2.0 pct plastic strain, the stress reaches a plateau and decreases subsequently, which is associated with the formation and thickening of twins as shown by high-resolution scanning transmission electron microscopy. At higher strain rates, the work hardening rate is significantly lower in the early deformation stage. The role of segregation to planar defects and the influence of local phase transformations (LPT) at SESFs is further discussed in reference to the influence of the strain rate. The segregation of W as an η stabilizing element is found to be crucial for the formation of a local phase transformation in ERBOCo-4. At higher strain rates the phase transformation is hindered by insufficient W segregation, resulting in a higher twin density.
CRIS-Team Scopus Importer:2023-02-24

Tailoring deformation mechanisms in polycrystalline CoNi-base superalloys for enhanced high temperature strength - Bezold, Andreas; Neumeier, Steffen (Scripta Materialia, 2023)
The significance of segregation processes during high temperature deformation in superalloys has become increasingly evident in recent years. Here, the importance of additionally tailoring the active deformation mechanisms is shown by correlating the strain-rate dependent high temperature strength of two slightly different polycrystalline CoNi-base superalloys with their underlying defect structures. Transmission electron microscopy investigations revealed that at high strain-rates shearing by APB-coupled dislocation pairs occurs in both alloys. With decreasing strain-rate, the deformation mechanism in one alloy transitions to stacking fault shearing and at very low strain-rates also to microtwinning, while APB-based shearing remains dominant in the other alloy. In comparison, stacking fault shearing induced a relative increase in strength of 200 MPa, which is diminished to 100 MPa as microtwinning becomes more prevalent implying that the high temperature strength of this alloy system can be significantly increased by tailoring the acting deformation mechanism.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Complex concentrated alloy; Creep; Deformation mechanisms; Stacking fault; Superalloy; Transmission electron microscopy

Temperature and Time Dependence of Elemental Segregation at Stacking Faults in Ni- and Co-Base Superalloys - Karpstein, Nicolas; Wu, Mingjian; Bezold, Andreas; Neumeier, Steffen; Cormier, Jonathan; Spiecker, Erdmann (Minerals, Metals and Materials Series, 2024)
Elemental segregation at stacking faults in the γ′ phase is a crucial part of the stacking-fault-based deformation of superalloys, and the local composition of a stacking fault critically affects the resistance of γ′ to further shearing. Here, the process of elemental segregation at extrinsic stacking faults in γ′ is examined in Ni-base superalloy CMSX-4 and Co-base superalloy ERBOCo-4. By measuring fault compositions not only after deformation, but also after additional load-free annealing steps of different durations and temperatures between 700 and 900 °C, time- and temperature-dependent aspects of the segregation process are revealed. It is shown that elemental segregation continues to evolve toward an equilibrium composition after a fault has formed, indicating that fully formed stacking faults still provide a driving force for segregation processes and that their equilibrium composition can differ from that which they obtain during their formation. As the elemental segregation process is diffusion-based, it is observed to be considerably slower at a lower temperature. In both alloys, the segregation trends observed after annealing depend on the annealing temperature: A lower temperature promotes a more γ-like fault composition associated with γ′ softening; conversely, at higher temperatures, the fault composition tends toward that of the η phase, which is considered beneficial in the context of local phase transformation strengthening. As η-like segregation also involves the enrichment of slowly diffusing tungsten, kinetics likely play a role in the observed temperature dependence.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Ni/Co-base superalloys; Phase transformation strengthening; Segregation; Stacking faults; Transmission electron microscopy

The Effect of Alloying on the Thermophysical and Mechanical Properties of Co–Ti–Cr-Based Superalloys - Zenk, Christopher; Volz, Nicklas; Bezold, Andreas; Huber, Laura-Kristin; Eggeler, Yolita; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Springer International Publishing, 2020)
The system Co–Ti–Cr was recently identified as a very promising base for low mass-density Co-based superalloys. This study presents the influence of quaternary alloying additions on the thermophysical and mechanical properties of a Co–11Ti–15Cr model superalloyModel superalloy. Al, Ta, Re, and W were selected as a starting point for alloy developmentAlloy development as they represent important alloying elements in both Ni-based and Co–Al–W-based superalloys. Microstructure analysis reveals that the addition of only 1 at.% of either of these elements causes the formation of different undesired intermetallic phases in addition to γ and γ′ phases, which is in agreement with thermodynamic calculations. However, a diffusion couple between the Co–Ti–Cr and a Co–Al–W–Ta alloy suggests that the tolerance for alloying elements without destabilizing the γ/γ′ two-phase microstructure is higher when they are present in a certain ratio. Energy-dispersive X-ray spectroscopy shows that Cr and Re are enriched in the γ phase, whereas Ti and W preferentially partition to γ′. All alloying elements increase the yield strength at room temperature, but are disadvantageous at 1000 °C. Re and W retain their strengthening effect up to 900 °C.

Unambiguous Stacking Fault Analysis for Unraveling Shearing Mechanisms and Shear-Based Transformations in the L12-Ordered γ′ Phase - Karpstein, N.; Lenz, Malte; Bezold, Andreas; Zehl, R.; Wu, Mingjian; Ludwig, A.; Laplanche, G.; Neumeier, Steffen; Spiecker, Erdmann (Proceedings of the 15th International Symposium on Superalloys, 2024)
With its precipitation strengthening effect, the L12-ordered γ′ phase contributes substantially to the mechanical properties of superalloys; therefore, understanding the microscopic mechanisms by which it can be sheared is of key importance. A commonly used method to study these mechanisms involves high-resolution imaging in the transmission electron microscope in <110> projection which enables straightforward discrimination between intrinsic and extrinsic stacking faults as well as microtwins. However, the complex or superlattice nature of these stacking fault structures, which provides key information on their formation mechanism, is not necessarily revealed in this projection. In the present work, an experimental approach is presented to resolve this ambiguity and reliably determine the complex or superlattice nature of a stacking fault in the L12 structure by additionally imaging the fault in a nearby <211> projection, which is achieved by tilting the specimen by 30°. The method is demonstrated using two different examples in single-crystalline Co-base superalloys. In the first example, the approach enabled the direct experimental verification of two key aspects of the well-known Kolbe mechanism for superlattice extrinsic stacking fault formation, namely, the complex nature of the leading intrinsic stacking fault segment and the occurrence of diffusion-mediated re-ordering. In the second example, microscopic details of the shear-based transformation from the cubic L12-γ′ to the hexagonal D019-χ phase are revealed, accounting for additional complexities—again including a re-ordering process—arising from the superlattice ordering of both phase
CRIS-Team Scopus Importer:2024-09-06
Keywords: Co-base superalloys; Deformation mechanisms; Phase transformations; Stacking faults; Transmission electron microscopy

Understanding creep of a single-crystalline Co-Al-W-Ta superalloy by studying the deformation mechanism, segregation tendency and stacking fault energy - Volz, Nicklas; Xue, Fei; Zenk, Christopher; Bezold, Andreas; Gabel, Stefan; Subramanyam, A. P.A.; Drautz, R.; Hammerschmidt, T.; Makineni, S. K.; Gault, B.; Göken, Mathias; Neumeier, Steffen (Acta Materialia, 2021)
A systematic study of the compression creep properties of a single-crystalline Co-base superalloy (Co-9Al-7.5W-2Ta) was conducted at 950, 975 and 1000°C to reveal the influence of temperature and the resulting diffusion velocity of solutes like Al, W and Ta on the deformation mechanisms. Two creep rate minima are observed at all temperatures indicating that the deformation mechanisms causing these minima are quite similar. Atom-probe tomography analysis reveals elemental segregation to stacking faults, which had formed in the γ′ phase during creep. Density-functional-theory calculations indicate segregation of W and Ta to the stacking fault and an associated considerable reduction of the stacking fault energy. Since solutes diffuse faster at a higher temperature, segregation can take place more quickly. This results in a significantly faster softening of the alloy, since cutting of the γ′ precipitate phase by partial dislocations is facilitated through segregation already during the early stages of creep. This is confirmed by transmission electron microscopy analysis. Therefore, not only the smaller precipitate fraction at higher temperatures is responsible for the worse creep properties, but also faster diffusion-assisted shearing of the γ′ phase by partial dislocations. The understanding of these mechanisms will help in future alloy development by offering new design criteria.<br
Keywords: Co-base superalloys; Directional coarsening; Creep; Stacking fault energy; DFT

Yielding behavior of a single-crystalline γ'-strengthened Co-Ti-Cr superalloy - Bezold, Andreas; Volz, Nicklas; Lenz, Malte; Zenk, Christopher; Spiecker, Erdmann; Mills, M. J.; Göken, Mathias; Neumeier, Steffen (Scripta Materialia, 2021)
The anomalous yielding behavior known from Ni3Al or Ni-base superalloys is explained by the formation of immobile dislocation configurations via cross-slip of the leading superpartial of anti-phase boundary-coupled dislocation pairs. A systematic investigation of the anomalous yielding behavior of a single-crystalline Co-11Ti-15Cr superalloy by transmission electron microscopy revealed the absence of similar sessile dislocation configurations during the initial yielding stage. Shearing of γ' precipitates via superlattice stacking fault formation is the dominant deformation mechanism at the peak temperature. Furthermore, the high density of superlattice stacking faults and their interactions also lead to a pronounced work-hardening anomaly.
Keywords: Superalloy; yield strength anomaly; work hardening; transmission electron microscopy (TEM); high-temperature deformation